Micro Perfusion and Quantitative Analysis of the Femoral Head Intraosseous Artery. Issue 1 (9th February 2018) - Qiu, Xing; Cheng, Liang‐liang; Wang, Ben‐jie; Liu, Bao‐yi; Yang, Lei; Yu, Mingyang; Gu, Guishan; Zhao, De‐wei
Abstract : The present study investigates the feasibility of micro perfusion of femoral head specimens from femoral neck fracture patients by the inferior retinacular arteries and performing intraosseous artery quantitative analysis of the femoral head. Twelve femoral neck fracture patients who had undergone conventional hip replacement surgery were included in this study. Femoral head specimen arteries were first dissected and exposed and then perfused by the inferior retinacular arteries and all the femoral heads underwent micro‐CT scanning. After micro‐CT scanning, a digital 3‐D model was reconstructed to quantify the femoral head intraosseous arteries for comparison with a normal femoral head. The artery length density, artery volume density, and artery length/volume ratio were calculated separately and compared with normal femoral head parameters. Micro‐CT scanning displayed the epiphyseal arterial network structure and their fine vascular branches in all 12 femoral neck fractures. Blood was supplied from the inferior retinacular artery to the epiphyseal arterial network then to all the fine blood vessels within the femoral head. No statistical differences were observed in femoral heads' intraosseous artery length densities or volume densities between the normal and femoral neck fracture specimens, while the artery length/volume ratio showed a statistical difference, and the ratio increased from 19 to 46. Micro perfusion of the femoral head by the inferior retinacular arteries is possible and can present the epiphyseal network and their fine arterial branches in pathologic conditions to provide a morphological basis for the study of femoral head disease.